POSSIBILITIES AND PROBLEMS OF THE TRANSITION TO A GREEN ECONOMY IN THE DEVELOPMENT OF THE REGIONAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2025)
The transition to a green economy represents a pivotal shift in addressing environmental challenges while fostering sustainable regional economic development. This paper explores the opportunities and challenges associated with adopting green economic practices at the regional level. Through an analysis of case studies and data-driven research, we identify key enablers, barriers, and strategies for successful implementation. The findings underscore the importance of policy alignment, technological innovation, and stakeholder collaboration in achieving a balanced and resilient regional economy. Moreover, the study highlights the role of economic diversification, renewable energy integration, and equitable growth in supporting sustainable development. Challenges such as financial constraints, policy gaps, and technological barriers are also discussed, emphasizing the need for targeted interventions. By examining the experiences of various regions, this paper provides actionable insights and a comparative framework for policymakers and stakeholders aiming to navigate the complexities of a green economic transition.